Complex investigations of the river Vardar. I. Approach and description of the investigations - Krstić, Svetislav; Melovski, Ljupčo; Levkov, Zlatko; Stojanovski, Panče (Macedonian Journal of Ecology and Environment, 1994)
This paper represents the fundamental principles of complex investigations on river Vardar that had been started in 1993. A detailed description of investigated area, theoretical principles of the applied methodology, description of up-to-date investigations are given and the possibilities for obtaining the precise data in establishing of a continual monitoring system for the control of harmful effects of polluted environment on live organisms are discussed. The investigations are postulated as an initial research in a complex ecological study necessary for the future realization of the project „Vardar valley,,.